Case report: Axilla fibroadenoma – An atypical presentation. (August 2022) - Virji, Safna Naozer; Vohra, Lubna Mushtaque; Abidi, Syeda Sakina; Idrees, Romana
Abstract: Introduction: Fibroadenoma is the most common benign breast tumor among women between 15 and 35 years, however, a fibroadenoma arising from accessory breast tissue is a rare occurrence. Case presentation: We encountered this uncommon presentation in a 37 years old female with a gradually increasing left axillary lump associated with discomfort. On ultrasound it was a 17.3 mm × 10.6 mm x 17.5 mm well defined solid nodule with internal vascularity, BiRADS IVa lesion. Core biopsy revealed fibroepithelial lesion and the patient electively underwent excisional biopsy. Histopathology confirmed the diagnosis of fibroadenoma, which was completely excised. Clinical discussion: Approximately half of all breast lumps in women are diagnosed as fibroadenomas, making it the most common benign breast mass. Nonetheless, an axillary mass has several differentials such as lymphadenopathy, lipoma or sebaceous cyst, while a fibroadenoma developed from ectopic breast tissue in the axilla is an unusual condition. Masses in axilla like ectopic breast tissue are clinically significant as they undergo physiological changes like the normal breast tissue like pain and discomfort during pregnancy, lactation and menstruation. This tissue may also undergo pathological changes and may pose a diagnostic challenge. Conclusion: Axillary lumps pose a diagnostic dilemma and accessory breast tissue related pathologies should be considered. Highlights: Axillary lumps may pose a diagnostic dilemma. Accessory breast tissue may undergo pathological changes and present as benign or malignant breast disease. Ectopic breast tissue should undergo routine annual screening.